PERSEBARAN EDELWEISS (Anaphalis spp.) PADA SUB TIPE HUTAN MONTANA DAN ALPIN DI TAMAN NASIONAL GUNUNG GEDE PANGRANGO - , RUNITA PARDIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Edelweiss (Anaphalis spp.) is a pioneer species that grows in volcanic soils in the open area of the mountains. Little information is known about edelweiss and its distribution in Gunung Gede Pangrango National Park. The purpose of this study was to determine species and distribution pattern of edelweiss in Mandalawangi and Surya Kencana Meadows in Gunung Gede Pangrango National Park. Inventory of edelweiss, which is a shrub, was conducted to identify its species and determine its class according to the height of the shrub. The shrub at class A refered to edelweiss which has the height â¤ 100 cm, while the shrub at class B refered to which has the height > 100 cm. Four plots were made at each transect. Two plots were made on the right and two plots were made on the left alongside a hiking trail, with a distance 20 m from the trail and inter plot. Transect was made and repeated every 100 m distance. The size of plot to determine the shrub at class A was 2 m x 2 m and the size of plot to determine the shrub at class B was 5 m x 5 m. The result showed that two species of edelweiss were found in Gunung Gede Pangrango National Park namely A. javanica and A. longifolia. Pattern of distribution of A. javanica for both class A and B in Mandalawangi was clustered, while the pattern of distribution of class A and B in Surya Kencana was regular and clustered respectively.